2003
DOI: 10.1039/b211895e
|View full text |Cite
|
Sign up to set email alerts
|

Using trimethylamine dehydrogenase in an enzyme linked amperometric electrode

Abstract: An amperometric enzyme electrode was studied based on the wild-type protein trimethylamine dehydrogenase (TMADH), which catalyses the oxidative N-demethylation of trimethylamine to produce dimethylamine and formaldehyde. Ferrocene derivatives were investigated electrochemically, as free diffusing electron acceptors for recycling of the prosthetic groups of the immobilised enzyme. Ferricinium had the highest rates but, inhibited the enzyme, possibly as a result of a conformational change initiated at the Val-34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Compared with enzyme-based sensors previously published [11][12][13][14][15][16][17][18], chemical modified sensors used in this study have a longer lifetime and do not require special conditions of temperature, humidity or light for conservation. In general, the stability of the enzyme-based sensors is lower than CPEs, and unless they are kept under specific conditions, their stability is guarantee only for a week [17].…”
Section: Sensing Properties Of Cpe and Spe Electrodesmentioning
confidence: 98%
See 1 more Smart Citation
“…Compared with enzyme-based sensors previously published [11][12][13][14][15][16][17][18], chemical modified sensors used in this study have a longer lifetime and do not require special conditions of temperature, humidity or light for conservation. In general, the stability of the enzyme-based sensors is lower than CPEs, and unless they are kept under specific conditions, their stability is guarantee only for a week [17].…”
Section: Sensing Properties Of Cpe and Spe Electrodesmentioning
confidence: 98%
“…Chemically modified electrodes (CME) containing surface-confined chemical functionalities exhibit some important advantages over conventional bare electrodes in terms of catalytic activity, selectivity and protection from fouling effects [10]. Determination of biogenic amines by using biosensors also represents an interesting alternative [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Loechel et al [9] also introduced a cysteine mutation of the residue Y442 in the protein trimethylamine dehydrogenase (TMADH) to couple into the protein's electron transfer pathway to facilitate charge transfer between enzyme and an electrode.…”
Section: Selected Amino Acid Coupling 21 Cysteine Couplingmentioning
confidence: 99%
“…Tamerler et al have suggested that hydroxyl and amine groups in methionine, lysine, serine, threonine, glutamine are important for improving adhesion in gold binding peptides. [58] This provided a method for modification of Au nanoparticles, that could then be attached to a SPR gold chip at a density of 1x10 9 particles/cm 2 to offer an antibody immobilization surface. With anti-Salmonella antibodies for detection of Salmonella typhimurium, the authors report a 10 fold improvement in detection, compared with classical SPR methodology.…”
Section: Au Binding Peptidementioning
confidence: 99%
“…Although histamine oxidase from Arthrobacter globiformis (a topaquinone-containing copper amine oxidase) has been used as a histamine sensor, this enzyme was found to be more sensitive for dopamine and tyramine than for histamine (2). Trimethylamine dehydrogenase (TMADH) 5 from Methylophilus methylotrophus (3) and the quinoprotein methylamine dehydrogenase from Paracoccus denitrificans (4) have been used in general amine-sensing electrodes without the complication of O 2 chemistry, but neither are as effective as histamine sensors.…”
mentioning
confidence: 99%